Community in Speed Space: Media Information About Ulumbu PLTP Geothermal - Franciska Anggelli , Tefbana; Bonar, Situmorang (Talenta Publisher, 2024)
Digitalization has caused the images of time and space to blur. The rapid flow of mediated information causes confusion and a lack of humanitarian awareness. This paper explains the reality of the Poco Leok case in the construction and expansion of the PLTP Ulumbu. Using Dromology theory by Paul Virilio in